What does empowerment mean to women in northern Ghana? Insights from research around a small-scale irrigation intervention - Bryan, Elizabeth; Garner, Elisabeth (International Food Policy Research Institute, 2020)
Women’s empowerment is important to improve the status of women and achieve greater gender equity. It is also an important vehicle for achieving other development goals related to food security, nutrition, health, and economic growth. Increasingly, researchers seek ways to measure women’s empowerment, trace the pathways through which women’s empowerment is achieved, and provide guidance for policymakers and practitioners aiming to facilitate women’s empowerment through their interventions. This paper explores local perceptions of empowerment in the Upper East Region of Ghana in the context of a small-scale irrigation intervention targeted to men and women farmers. Using data collected through qualitative interviews and focus groups, the paper traces the linkages between small-scale irrigation and aspects of women’s empowerment, identified as important to men and women farmers themselves. The relationship between the components of empowerment and small-scale irrigation are placed within a larger context of social change underlying these relationships. Finally, this paper explores the ways that the introduction of modern technologies for small-scale irrigation may contribute to women’s empowerment.